Antagonistic effects of 3 sesquiterpene lactones from Atractylodes macrocephala Koidz on rat uterine contraction in vitro - Zhang Yi-Qiang; Xu Shi-Bo; Lin Yong-Cheng; Li Qun; Zhang Xiao; Lai Ying-Rong (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of three sesquiterpene lactones: atractylenolide I (8,9-dehydroasterolide, B), 4,15-epoxy-8 beta-hydroxyasterolide (C), and atractylenolide III (8 beta-hydroasterolide, D) from Atractylodes macrocephala Koidz, on rat isolated uterus smooth muscle. METHODS: Rat isolated uteri bathed in De Jalon I solution were used; acetylcholine (ACh), CaCl2, and oxytocin (Oxy) were used to evoke the contraction of uterus. RESULTS: B, C, and D 28 or 56 mumol.L-1 inhibited the spontaneous movement of uterus, reducing their rest force, contractile force, and movement ability. B 28 or 56 mumol.L-1 also slowed down the frequency of uterus spontaneous contraction, but C or D did not. B, C, or D 28 and 56 mumol.L-1 inhibited the uterine spasm induced by Oxy and ACh. Likewise, Ver 0.28 mumol.L-1, B, C, and D 28 or 56 mumol.L-1 relieved the contraction mediated by CaCl2 in high-KCl solution, but B, C, or D had not marked influence on the maximal response of uterus to CaCl2. CONCLUSION: B, C, and D inhibit the movement of uterus smooth muscle, and the mechanism is related to the inhibition of cholinergic system as well as Ca2+ movement.